Perbandingan Survei dan Analisis Data Geolistrik Sounding Daerah Pantai dan Pegunungan Studi Kasus Penyelidikan Air Tanah di Kabupaten Kendal, Jawa Tengah - Imam Suyanto (Department of Physics, Sebelas Maret University, 2016)
A geoelectrical method research have been done to find out the presence of aquifer at mountain and coastal area in Kabupaten Kendal, Central java, February 2008 using VES (Vertical Electrical Sounding) method, Schlumberger configuration. 22 measurement location spread out at coastal and mountain area with the 500 meter long each measurement point. Each measurement point presented in resistivity curve and the thick of each detected subsurface layer asa result of Progress III data processing software. From the result of this measurement shown that the aquifer at coastal area defined as confined a aquifer with the range of thickness more than 50 meter thick and the range of resistivity value between 5 – 15 Ohm meter and the eksistence of the detected subsurface layer shown mostly at each sounding point. For the mountainarea, the the deep of the aquifer around hundred meters at the subsurface with the range ofthickness about 10-20 meters with the range of resistivity value 10-80 Ohm meter.